1991
DOI: 10.1126/science.254.5037.1489
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transformations in Carbon Fullerenes at High Shock Pressures

Abstract: C(60) powders were shock-compressed quasi-isentropically and quenched from pressures in the range 10 to 110 GPa (0.1 to 1.1 Mbar). Recovered specimens were analyzed by Raman spectroscopy and optical microscopy. C(60) fullerenes are stable into the 13- to 17-GPa pressure range. The onset of a fast ( approximately 0.5 micros) reconstructive transformation to graphite occurs near 17 GPa. The graphite recovered from 27 GPa and about 600 degrees C is relatively well ordered with crystal planar domain size of about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(35 citation statements)
references
References 22 publications
2
32
0
1
Order By: Relevance
“…2a and b), which indicates that the carbon fullerene was still in a stable state. This result is consistent with that reported by Yoo and Nellis [1], who demonstrated that carbon fullerene is stable up to at least 17 GPa under shock wave compression. However, when the 913…”
supporting
confidence: 93%
See 1 more Smart Citation
“…2a and b), which indicates that the carbon fullerene was still in a stable state. This result is consistent with that reported by Yoo and Nellis [1], who demonstrated that carbon fullerene is stable up to at least 17 GPa under shock wave compression. However, when the 913…”
supporting
confidence: 93%
“…Under shock wave loading conditions, Yoo and Nellis [1] demonstrated that carbon fullerenes are stable below 17 GPa, and completely transform to graphite at 27 GPa. At higher pressures, products were mainly graphite and amorphous carbon; no diamond phase was observed.…”
mentioning
confidence: 99%
“…( v ) synthesizing metastable materials, [58][59][60] (vi) synthesizing carbon phases from C-60, [61][62][63] (vii) inducing enormous densities of shock-induced defects which alter physical properties (superconductors have higher critical current densities [64][65][66][67][68] and permanent magnets are more permanent 6 9 ) , (viii) crystallographically oriented shock compacts, 7 0 (ix) shocking oriented crystals at an angle to the impactor to maximize defect generation without fracturing the sample, 7 1 (x) shock compacting ceramic powders to get high densities with microstructural features which would enhance performance, [72][73][74][75] (xi) shock compaction of metastable materials to make consolidated powder compacts by working completely out of the equilibrium phase diagram, 76 (xii) comparing experimental data with a computer code which simulates shock compaction of powder particles, 77,78 (xiii) shock-induced amorphization, …”
Section: E Materials Recovered From High Shock Pressuresmentioning
confidence: 99%
“…Highly strong construction materials may be obtained by bulk compression of fullerene condensates (fullerites). Pioneering work in this field was performed by several research groups [6][7][8][9]. When pressure is about 1 GPa and temperature is 200…”
Section: Introductionmentioning
confidence: 99%